Cardiac CT Assessment of Left Atrial Appendages Anatomy in Patients Undergoing Coronary CT Angiography - Ejaz, Muhammad; Khan, Bakht Umar; Muhammad, Tayyeb; Iqbal, Muhammad Adnan (Biological and Clinical Sciences Research Journal, 2025)
The left atrial appendage (LAA) is an anatomical, finger-like projection that arises from the left atrium (LA), characterized by unique anatomical and physiological properties distinct from those of the main atrial body. Embryologically, the LAA represents a remnant of the primordial left atrium. The morphological diversity of the left atrial appendage (LAA) is clinically significant, influencing the risk of thromboembolic events and the management strategies in patients with cardiac disease. This study aimed to evaluate the frequency distribution of four distinct morphological types of the LAA among patients undergoing cardiac imaging. Objective: To determine the frequency of four morphological types (chicken wing, windsock, cauliflower, and cactus) of the left atrial appendage using cardiac computed tomography (CT). Methods: A cross-sectional descriptive study was conducted at the Cardiac Imaging Section, Medical Teaching Institute - Hayatabad Medical Complex, Peshawar, Pakistan, from July 22, 2022, to January 22, 2023. All included patients underwent imaging using a minimum 64-slice cardiac CT scanner, without preference for a specific vendor. Patients presented in a non-fasting state to ensure consistent loading conditions of the left atrium, as fasting state variations could affect the assessment of LAA morphology. Results: Out of 167 patients, the chicken wing morphology was the most prevalent, identified in 57 patients (34.1%). The cactus morphology was observed in 40 patients (24.0%), followed by the windsock morphology in 39 patients (23.4%), and the cauliflower morphology in 31 patients (18.6%). Conclusion: This study highlights chicken wing morphology as the predominant type among patients attending cardiac imaging at our institution, followed by cactus, windsock, and cauliflower types. Awareness of the prevalence and distribution of LAA morphologies within specific populations can aid in clinical decision-making, particularly in assessing stroke risk and developing personalized therapeutic approaches.